Three-Component Process for the Synthesis of Pyrimido[2,1-c][1,2,4]triazine Derivatives via Knoevenagel Condensation Under Thermal Aqueous Conditions - A. Saad, Hosam; R.E. >Aly, Mohamed; H. Abdel-Hafez, Shams (Current Organic Synthesis, 2015)
A Knoevenagel one-pot synthesis of 6-amino-4-oxo-8-(2-thienyl)-3-[2-(2-thienyl)vinyl]-4H-pyrimido[2,1- c][1,2,4]triazine-7-carbonitrile 2 via the reaction of 3-amino-6-[2-(2-thienyl)vinyl]-1,2,4-triazin-5(4H)-one 1 with thiophene- 2-carbaldehyde and malononitrile under basic conditions is described. New fused heterotricyclic nitrogen systems, such as pyrimido[5',4':5,6]pyrimido[2,1-c][1,2,4]triazine 5, 7, 9, 12, 13, 20 and pyrido[3',2':5,6]pyrimido[2,1- c][1,2,4]triazine 10, 11, 14 were achieved by treating 2 with cyanamide, urea, thiourea, and CS2 in ethanolic ethoxide, formamide, triethyl orthoformate and then ammonia, malononitrile, ethyl cyanoacetate, chloroacetyl chloride and phenyl isothiocyanate. The structures of the products have been deduced from their elemental analysis and spectral data (IR, 1H-NMR, 13C-NMR). The antimicrobial activity of all synthesized compounds was screened.
Keywords: 1-c][1